Insights into the synthesis, engineering, and functions of microbial pigments in Deinococcus bacteria - Wang, Yuxian; Liu, Jiayu; Yi, Yuanyang; Zhu, Liying; Liu, Minghui; Zhang, Zhidong; Xie, Qiong; Jiang, Ling (Frontiers in Microbiology, 2024)
The ability of Deinococcus bacteria to survive in harsh environments, such as high radiation, extreme temperature, and dryness, is mainly attributed to the generation of unique pigments, especially carotenoids. Although the limited number of natural pigments produced by these bacteria restricts their industrial potential, metabolic engineering and synthetic biology can significantly increase pigment yield and expand their application prospects. In this study, we review the properties, biosynthetic pathways, functions of key enzymes and genes related to these pigments and explore strategies for improving pigment production through gene editing and optimization of culture conditions. Additionally, studies have highlighted the unique role of these pigments in antioxidant activity and radiation resistance, particularly emphasizing the critical functions of deinoxanthin in D. radiodurans. In the future, Deinococcus bacterial pigments will have broad application prospects in food industry, drug production and space exploration where they can serve as radiation indicators and natural antioxidants to protect astronauts' health during long-term space flights.